Curious George. Spooky fun [videorecording (DVD)]. - Bennett, Jeff, 1962- (Curious George (Television program), 2006)
Tag along with Curious George on his spooky fun adventures. In this six-episode collection, everyone's favorite monkey conquers his fear of the dark in a power outage, helps a lost baby possum find his way home, creates a stir searching for mysterious night-time creatures and much more.